Functional Amenorrhea and Pituitary Microadenoma - Dan Nicolae PADURARU (Modern Medicine, 2019)
Introduction: Functional hypothalamic amenorrhea is a diagnostic challenge, especially in association with structural pituitary changes. We present the case of a patient with functional amenorrhea and pituitary microadenoma, evaluated in multiple medical centres. Case report: A 27-year-old female was referred to our clinic for secondary amenorrhea installed 18 months prior, insomnia, polydipsia (around 4-6 l water intake/day) and polyuria. Clinical examination revealed an underweight patient, with BMI (Body Mass Index) of 17.5 kg/m2, normal secondary sex characteristics, pallor of the skin and mucosa. The hormonal profi le revealed normal FSH (Follicle Stimulating Hormone) levels, low LH - Luteinizing Hormone (of 0.15 U/L, normal: 1.20-12.8 U/L), estradiol (of 11.2 pg/mL, normal: 49-291 pg/mL) and progesterone (of 1.13 ng/mL, normal: 5.16-18.56 ng/mL). No pathological changes were recorded at somatotropic, lactotropic, thyrotropic and corticotropic levels. The Diphereline stimulation test revealed functional integrity of the pituitary gland and ovaries. The progesterone with drawal test was negative. There were no pathological fi ndings on biochemical workup and the water deprivation test excluded diabetes insipidus. Morphological exploration of the hypothalamic-pituitary region by contrast-enhanced MRI (Magnetic Resonance Imaging) scan revealed a left pituitary microadenoma measuring 5 mm in diameter. Adequate diet and oral contraceptive treatment were recommended. Conclusion: Functional hypothalamic amenorrhea (FHA) is the most common cause of neuroendocrine amenorrhea. Identifying the context and causative factors is essential for making an appropriate therapeutic decision.